Poems $1 (BVolume 3s - Meredith, George, 1828-1909 (Salt Lake City, UT : Project Gutenberg, 1998)
"Poems $1 (BVolume 3" by George Meredith is a collection of poetry written during the late 19th century. This volume features a diverse array of themes, exploring human experiences, emotions, nature, and the complexities of love and relationships. Through his intricate verses, Meredith invites readers to reflect on profound philosophical questions and societal observations. The opening of this work introduces readers to Meredith's lyrical style, beginning with the poem "A Stave of Roving Tim." Here, we meet the character of Roving Tim, who embodies a carefree spirit, wandering through life with a humorous perspective on nature and the drawbacks of conventional living. The subsequent poem, "Jump-to-Glory Jane," presents a widow whose sudden transformation leads her into an exhilarating and transformative dance, captivating and bewildering her community. As the narrative unfolds, the themes of joy, love, and the societal response to those who deviate from the norm are established, providing a glimpse into the rich tapestry of Meredith's poetic exploration. (This is an automatically generated summary.)s
Release date is 1998-07-01
Transcribed from the 1912 Times Book Club (3z(BSurrey(3y (Bedition by David Prices
Keywords: English poetry; Didactic poetry